Cash Flow Statement Analysis as a Decision-Making Tool in Financial Management: (A Case Study of PT. Indofood Sukses Makmur) - Dipoatmodjo, Tenri Sayu Puspitaningsih (International Humanity Advance, Business & Sciences, 2024)
Financial planning, analysis, and control of financial operations are examples of tasks that fall under the field of financial management. The purpose of this research is to examine and analyze the cash flow statement to gain valuable insights for decision-making. To conduct this analysis, the author uses a qualitative descriptive research approach. They collect, transform, interpret, and analyze data to summarize the results from revenue. The cash flow statement for the food and beverage industry is prepared by PT Indofood Sukses Makmur. When calculating all cash flow metrics, the average revenue—or net profit—is quite large. The cash flow calculation results show the company's profit and the growth percentage of each result; Indofood Sukses Makmur is a company that shows very low sales. PT Indofood generates the lowest average cash flow statement ratio compared to all other food and beverage companies studied in this research.